Are soil‐adjusted vegetation indices better than soil‐unadjusted vegetation indices for above‐ground green biomass estimation in arid and semi‐arid grasslands?. (8th December 2014) - Ren, H.; Feng, G.
Abstract Accurate estimation of grassland biomass has been a central focus due to its importance in ecosystem processes and carbon cycles. This study aimed to examine whether the performance of soil‐adjusted vegetation indices for estimating above‐ground green biomass was better than that of soil‐unadjusted vegetation indices in arid and semi‐arid grasslands. Above‐ground green biomass in desert steppe of Inner Mongolia and corresponding moderate‐resolution imaging spectroradiometer (MODIS) surface reflectance 8‐day composite MOD09Q1 data were collected during late September of 2013. Results showed that soil‐adjusted SAVI (soil‐adjusted vegetation index), MSAVI (modified soil‐adjusted vegetation index), OSAVI (optimized soil‐adjusted vegetation index), TSAVI (transformed soil‐adjusted vegetation index), ATSAVI (adjusted transformed soil‐adjusted vegetation index) and PVI (perpendicular vegetation index) did not improve estimation accuracy over soil‐unadjusted simple ratio (SR) and normalized difference vegetation index (NDVI), due to low green vegetation cover (<30%) in the study area. Our results suggest that these soil‐adjusted vegetation indices may be not suitable for describing green vegetation information in arid and semi‐arid grasslands with low green vegetation cover (<30%).